Comparative evaluation of calcium ion release of two commercially available pulp capping agents at different time periods: An in vitro study - R. J. Kakodkar; K. Y. Bhargava; S. A. Mulay; A. J. Pai Khot; S. G. Shirsath; H. R. Nihalani (Эндодонтия Today, 2025)
INTRODUCTION. Vital pulp therapy is a significant approach in restorative dentistry, enabling the preservation of pulp vitality and the stimulation of hard tissue repair. Modern pulp capping materials, particularly silicate-based cements, facilitate dentin bridge formation and promote tissue remineralization.TheraCal LC and ApaCal ART are two commercially available materials with bioactive properties and the ability to release calcium ions, contributing to pulp healing. However, there is limited literature on the bioactivity of ApaCal ART. This in vitro study aims to comparatively evaluate the calcium ion release from TheraCal LC and ApaCal ART using the EDTA titration method. The null hypothesis assumes no statistically significant differences between the tested materials.AIM. The study aimed to compare and evaluate the calcium ion release of two commercially available pulp capping agents TheraCal LC and ApaCal ART at different time periodsMATERIALS AND METHODS. This in vitro study was conducted following good laboratory practice guidelines and approved by the institutional review board (Approval No. [DYPDCH/DPU/EC/582/142/2023]). Twenty cylindrical specimens (6 mm × 3 mm) were prepared using silicon molds and divided into two groups: TheraCal LC (n = 10) and ApaCal ART (n = 10). A dental floss was incorporated into each mold before filling with the respective material. TheraCal LC was light-cured for 20 seconds, and ApaCal ART for 40 seconds. The specimens were weighed for standardization and incubated in deionized water at 37°C and 100% humidity for 24 hours. Specimens were immersed in 5 mL of distilled water and assessed at 24 hours, 7 days, and 21 days. The solution was refreshed at each time point, and calcium ion concentration was measured using the EDTA titration method. Data were analyzed using IBM SPSS® Statistics 21.0. Intragroup comparisons were performed using repeated measures ANOVA with Tukey’s post-hoc test, and intergroup comparisons with an unpaired t-test (p < 0.05 considered statistically significant).CONCLUSIONS. The study demonstrated that TheraCal LC and ApaCal ART exhibited a progressive increase in calcium ion release over time, reaching a peak on day 21. TheraCal LC released significantly more calcium ions at all time points and may be preferable for indirect pulp capping due to its enhanced stimulation of hard tissue formation.